OPTIMASI KOMPOSISI KIRIMAN TEBU UNTUK MENCAPAI HASIL GULA OPTIMAL DI PT. INDOLAMPUNG PERKASA KABUPATEN TULANG BAWNAG, LAMPUNG - Tri Sunu Budi Artha; Dwidjono Hadi Darwanto; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
Sugarcane in PT.ILP harvested by harvesting division through logging, unloading and transport. Logging is done in the form of sugar cane burn. The existence of a span of fuel to burn the sugar cane milling can undergo metabolism that cause decomposition of biodegradable polysaccharides or disaccharides, resulting in reduced cane sugar. Therefore, logging and proper and efficient transport can reduce the rate of decline in the value of pol and purity. Logging and transport in PT.ILP is done in three systems, namely Bundle Cane, Loose Cane, and Chopped Cane.This study aimed to determine : (i) differences in the ability of the system to send Cane Bundle, Loose Cane and Chopped Cane, and (ii) the composition of the optimal delivery system Cane Bundle, Loose Cane, and Chopped Cane. This study used a descriptive analytical method. The type of data collected and analyzed secondary data of sugarcane to the factory shipment in 2012 and in 2013 from Harvesting Division PT.ILP be burnt to crush report time (hour) per weeks. Methods of data analysis using quantitative analysis method of linear programming models.The result showed that there are differences in the average shipment of sugar cane to the factory PT.ILP systems Bundle Cane, Cane Loose, and Chopped Cane Cane Bundle cutting system where the highest followed Loose Cane cutting system. In addition, the result of the study also concluded that the average composition of the shipment of cutting system Bundle Cane, Cane Loose, and Chopped Cane currently not optimal in meeting the quota factory. This is evident from the composition of the shipment allocation of sugarcane to the factory PT.ILP on each cutting system (Bundle Cane, Cane Loose, and Chopped Cane) to change the composition of the previous allocation so that a change in the composition is still obtainable sugar production higher than before (still can be improved). A change in the number of workers cutting and variable costs per ton cane will change the composition of the optimal number of items cane to the mill.